Gender specific land-use decisions and implications for ecosystem services in semi-matrilineal Sumatra. (July 2016) - Villamor, Grace B.; van Noordwijk, Meine
Graphical abstract: Highlights: Gender-differentiated land-use choices affect ecosystem service delivery. Experimental games showed (agro)forest conversion decisions are gender specific. With an agent-based model we explored how this can be represented and understood. Decisions differ from standard models through bounded rationality, willpower and self-interest. Gender specificity of expression of the three bounds can inform new generic theory. Abstract: Gender specificity with respect to land-use options and responsiveness to agents that offer related investment opportunities is poorly understood. We combined agent-based modeling and experimental role playing games to compare land-use preferences and decisions between men and women in a landscape dominated by rubber agroforests in Sumatra, Indonesia. Ecosystem service delivery can be influenced by gender specific land-use preferences, especially in areas under conservation agreements. The research methods were designed to examine gender aspects of three 'bounds' of human nature ( bounded rationality, bounded willpower and bounded self-interests ) in relation to land-use decisions. Rice fields (mostly owned and inherited by females) provide part of local staple food needs in the study area, whereas rubber agroforests provide income in addition to resources for local use and rubber and oil palm monocultures are fully market oriented. In both the model and game exercises, men preferred the status quo rice production in combination with agroforest land uses, but women preferred the conversion of agroforest to more financially profitable monoculture systems, with increased carbon emissions as side effect. Although both genders exhibited similar preferences for ecosystem service provision, regulatory ecosystem services (i.e., climate and water regulation) were reduced by women's landuse choices. Thus, ecosystem service tradeoffs are potentially greater in women-dominated landscapes under these circumstances. Furthermore, gender-specific limitations and socio-cultural contexts (i.e., matrilineal societies) may influence the flow of ecosystem services as well as landscape patterns.